Integrative Teaching in Radiology – A Survey - Authors; Authors; Dettmer, S.; Weidemann, J.; Fischer, V.; Wacker, F. K.; German Association of Chairmen in Academic Radiology (KLR); German Association of Chairmen in Academic Radiology (KLR); Adam, G.; Antoch, G.; Barkhausen, J.; Beer, M.; Bley, T.; Bücker, A.; Claussen, C. D.; Düber, C.; Forsting, M.; Hamm, B.; Hauenstein, K.; Heindel, W.; Hosten, N.; Jansen, O.; Kahn, T.; Kauczor, H. U.; Krombach, G.; Kuhl, C.; Langer, M.; Laniado, M.; Lotz, J.; Mahnken, A.; Maintz, D.; Nikolaou, K.; Reiser, M.; Ricke, J.; Rummeny, E.; Schild, H.; Schönberg, S.; Spielmann, R. P.; Stroszczynski, C.; Teichgräber, U.; Uder, M.; Vogl, T. J.; Wacker, F.; German Radiological Society (DRG) – Executive Board; German Radiological Society (DRG) – Executive Board; Vorwerk, D.; Anton, F.; Romahn, J.; Lohwasser, S. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To survey integrative teaching in radiology at German universities.Materials and Methods: A questionnaire about radiological education was sent electronically to all 37 chairpersons of university radiology departments in Germany. The questions included the course type, teaching methods, concept, perception, and advantages and disadvantages of integrative teaching. Statistical analysis was performed with nonparametric statistics and chi-square test.Results: The survey was considered representative with a return rate of 68 %. Integrative teaching is established at 4/5 of all departments. Integrative teaching is well accepted with an acceptance rate that is significantly higher in so-called “Modellstudiengängen” [model courses of study] (100 %) compared to conventional courses of study (72 %). The advantages of integrative teaching include linking of content (92 %) and preparation for interdisciplinary work (76 %). The disadvantages include high effort (75 %) and time (67 %) for organization. Furthermore, there is a risk that basic radiological facts and knowledge cannot be conveyed and that the visibility of radiology as an independent discipline is lost. Conventional radiological teaching has a similarly high acceptance (84 %) compared to integrative courses (76 %).Conclusion: Integrative teaching has a high acceptance among chairpersons in radiology in Germany despite the greater effort. A good interdisciplinary collaboration is essential for integrative teaching and at the same time this can be conveyed to the students. However, the visibility of radiology as a discipline and the possibility to cover basic radiological content must be ensured. Therefore, both conventional courses and integrative teaching seems reasonable, especially in cross-disciplinary subjects such as radiology.Key Points• Both integrative teaching and conventional radiological teaching are highly accepted. The advantages include the linking of multidisciplinary content and the preparation for interdisciplinary cooperation. The disadvantages include more time and effort for organization and reduced visibility of cross-disciplinary subjects.Citation Format:• Dettmer S, Weidemann J, Fischer V et al. Integrative Teaching in Radiology – A Survey 2015; 187: 260 – 268
Keywords: student teaching; medical education; radiological teaching; integrative teaching